Public administration tasks for the protection of agricultural and forest land in Poland - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2012)
Public administration tasks for the protection of agricultural and forest land in Poland include the implementation of a universally binding law. In this way, a new reality is shaped in agriculture and rural areas, implementing standards of the European Union into the Polish reality. This applies especially in reference to the protection of the environment and complying with the intended use of agricultural and forest land.